The theory and practice of exchange control in Germany: a study of monopolistic exploitation in international markets - Child, Frank C. (The Hague : M. Nijhoff, 1958)
This book attempts to highlights the nature of German trading practices during the pre-war days of the Nazi regime. It also tried to explain that exchange control is a useful and flexible implement of commercial policy and that appropriate regulations will, for any one nation, increase or even maximize the gains from external trade.
Includes index
Bibliography: p. [231]-237.
usc 10/08/18
Loans
Keywords: Foreign exchange; Commercial policy; Foreign exchange rates; Economics; Germany